Application of Rodamine B Optical Detector in Environmental and Food Analysis - Kazemzadeh, A.; Kavei, G. (Asian Journal of Chemistry, 2010)
An optical oxalic acid detector was developed by immobilizing a direct indicator dye in an optical detecting film for food and environmental monitoring by FIA. This detector was fabricated by binding rhodamine B to a cellulose acetate film that had previously been subjected to an exhaustive base hydrolysis. The membrane has good durability (> 5 months) and a short response time (< 9 s). Oxalic acid can be determined for the range 0.07-3.50 μg mL-1 with 36 detection limits of 12 ng mL-1. The method is easy to perform and uses acetyl cellulose as a carrier. The reagents used for activating the cellulose support are inexpensive, non-toxic and widely available.